Freedom Celebration: A Juneteenth Party - Dalton, Angela; Morris, Keisha ([Place of publication not identified] : Harper Collins, 2025)
"The Morris family celebrates Juneteenth together every year with a barbeque including red food and drinks. Gloria and Grandma Daisy explain why Juneteenth is called Freedom Day and why we celebrate this important date"
new kids book 2025 spring.
Keywords: Juneteenth; African American families; Social Life and Customs; Family reunions; African Americans; Anniversaries; Parties